2018
DOI: 10.1155/2018/9054301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Load Cycling on the Fracture Strength/Mode of Teeth Restored with FRC Posts or a FRC Liner and a Resin Composite

Abstract: The aim of the study was to comparatively evaluate the fracture strength and mode of root canal treated teeth restored with resin composites with and without posts. The lingual cusps of root canal treated first upper premolars (n = 10/group) were removed down to cervical enamel and restored with the following: group A: glass-fiber post (Glassix) followed by a particulate-filled composite resin (PFC, G-aenial posterior, 3 × 2 mm layers); group B: glass-fiber reinforced composite bulk fill liner (EverX posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 53 publications
0
15
0
3
Order By: Relevance
“…In the CB group, maximum von Mises stresses in dentin could be noted on the bottom of the post preparation cavity, rather than on the vestibular cervical portion of the tooth as in the other investigated groups. It seems that the post absorbed a certain amount of the stresses, but also transported them to the root portion of the tooth, and could hence potentially act as a wedge leading to catastrophic tooth fracture, as demonstrated in vitro 31 . This is in accordance with the report of a reduced stress concentration on the inner wall of the root in premolars restored with an endocrown compared to a post, core and crown restoration 32 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the CB group, maximum von Mises stresses in dentin could be noted on the bottom of the post preparation cavity, rather than on the vestibular cervical portion of the tooth as in the other investigated groups. It seems that the post absorbed a certain amount of the stresses, but also transported them to the root portion of the tooth, and could hence potentially act as a wedge leading to catastrophic tooth fracture, as demonstrated in vitro 31 . This is in accordance with the report of a reduced stress concentration on the inner wall of the root in premolars restored with an endocrown compared to a post, core and crown restoration 32 .…”
Section: Discussionmentioning
confidence: 84%
“…There were larger areas under medium level stresses in the root portion of the teeth, and in the C model, the highest stress area moved from the vestibular cervical portion to the bottom of the post preparation cavity. This could further imply (along with the maximum von Mises stress and strain values) that clinically, the post could cause a wedge and lead to root fracture 22 , 31 . A recent review on validated FEA studies in dentistry reported that although the teeth in the in vitro validation experiments were mostly embedded in epoxy resin, composite resin, or silicone, in the corresponding FEA study, PDL and/or bone were modelled 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that some factors can modify the hardness and surface characteristics of restoration materials and the health of peri-implant tissues. One of these factors is cyclic loading [ 63 ], which can affect a multi-unit abutment screw and create a weak point that results in prosthetic complications [ 64 ]. An acid environment and polishing procedures also can affect surface roughness, microhardness, and flexural strength of ceramics [ 65 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Improved mechanical properties can increase the success of composite restorations, especially in large cavities with large occlusal force. [7][8][9] Studies have been conducted to improve and strengthen the mechanical properties of composite resin with the addition of fiber. Research studies suggest that fiber-reinforced composites as structures under composite restorations can increase the load-bearing capacity and modify stresses by creating a monoblock effect, thereby helping to distribute and transfer stresses along the long axis of the teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies suggest that fiber-reinforced composites as structures under composite restorations can increase the load-bearing capacity and modify stresses by creating a monoblock effect, thereby helping to distribute and transfer stresses along the long axis of the teeth. 7,8,10,11 Stress analysis due to masticatory forces can be performed by using the finite element method (FEM) to identify highstress concentrations that result in restoration failure. 12 The advantages of FEM are reduced research time and costs, as well as provide an overview of a new scientific concept to clinical application, by carrying out the virtual test under measured and conceivable loading conditions.…”
Section: Introductionmentioning
confidence: 99%